MODEL HUBUNGAN INTERPERSONAL MASYARAKAT MUSLIM DAN NON MUSLIM GUNA MENJAGA KERUKUNAN UMAT BERAGAMA PADA KECAMATAN BESITANG KABUPATEN LANGKAT - Wahyu Ziaulhaq (Yayasan Literasi Sains Indonesia, 2022)
This study seeks to describe the model of interpersonal relationships between Muslim and nonMuslim communities in order to maintain religious harmony. The main purpose of this research is to educate the readers that the residents of Besitang District live side by side in harmony despite religious differences. The method used in this research is qualitative research which produces descriptive data in the form of written or spoken words. Data collection techniques using interviews (in-depth interviews). Then the data analysis technique used in this research is data reduction, data presentation and conclusion verification. From the results of this study, it has been found that the model of interpersonal relationships among Muslim and non-Muslim communities in Besitang District is mutual cooperation in the social field, always conducts deliberation between religious communities and has a sense of mutual care for others, has emotional bonds that respect each other. in religious differences. Therefore, it can be concluded that there are values of inter-religious harmony in Besitang District. The absence of herinzontal conflicts between religious adherents.